Magical moments in medicine Part 6: Renaissance medicine - Judson, John Paul (Faculty of Medicine, University of Malaya, 1999)
The period between the last breath of the medieval night and the first glimpse of dawn of the next era is a dreary 75 years, during which we see no spectacular happenings. After the devastating medieval Black Death in 1347 AD, the process of medical evolution appears to have taken along sabbatical. Demoralized physicians and barber surgeons.who could offer no cure for the plague epidemic, lost their credibility with the public and therefore, lapsed into oblivion. Shakespeare's comment' trust not the physician; his antidotes are poison" in Timon of Athens (1607) therefore, does not strike us as bizarre.